On the Automaticity of Attentional Orienting to Threatening Stimuli - Anderson, Brian A. (Emotion, 2019)
Attention is biased towards stimuli that have been associated with aversive outcomes in the past. This bias has previously been interpreted as reflecting automatic orienting toward threat signals. However, in many prior studies, either the threatening stimulus provided valuable predictive information, signaling the possibility of an otherwise unavoidable punishment and thereby allowing participants to brace themselves, or the aversive event could be avoided with fast and accurate task performance. Under these conditions, monitoring for threat could be viewed as an adaptive strategy. In the present study, fixating a color stimulus immediately resulted in a shock on some trials, providing a direct incentive not to look at the stimulus. Nevertheless, this contingency resulted in participants fixating the shock-associated stimulus more frequently than a neutral distractor matched for physical salience. Our findings demonstrate that threatening stimuli are automatically attended even when attending such stimuli is actually responsible for triggering the aversive event, providing compelling evidence for automaticity.